Mechanisms of hepatocellular carcinoma and cirrhosis development in concurrent steatotic liver disease and chronic hepatitis B - Saisai Zhang; Lung-Yi Mak; Man-Fung Yuen; Wai-Kay Seto (Clinical and Molecular Hepatology)
Chronic hepatitis B (CHB) poses a major global public health challenge and is a leading cause of cirrhosis and liver cancer. Hepatic steatosis is common in individuals with CHB compared to the non-CHB population and is particularly prevalent in hepatitis B virus (HBV)-endemic regions, affecting about one-third of CHB patients. The interaction between hepatic steatosis and CHB-related disease progression is complex and still under debate. Evidence demonstrates that co-existing steatosis may worsen liver fibrosis while paradoxically increasing the likelihood of achieving better HBV control. In particular, despite the association of steatotic liver disease (SLD) with lower HBV viral loads and higher rates of HBsAg seroclearance, the coexistence of CHB and SLD can potentially accelerate liver disease progression. Factors such as fat deposition, lipotoxicity, oxidative stress, and chronic inflammation in SLD may foster a pro-fibrotic and pro-carcinogenic environment, accelerating the disease progression. Additionally, loss of global DNA methylation, changes in the immune microenvironment, and genetic susceptibility further contribute to the development of CHB-related cirrhosis and hepatocellular carcinoma (HCC). This review examines the mechanisms driving liver disease progression and the heightened risk of cirrhosis and HCC in patients with concurrent CHB and steatotic liver disease, underscoring the importance of prioritizing antiviral therapy for CHB in addition to addressing SLD.